IMPELEMENTASI POTENTIAL HAZARDS PELAYANAN RUMAH SAKIT DENGAN MENGGUNAKAN METODE JOB SAFETY ANALYSIS - Katiandagho, Dismo; Layuk, Semuel; Rokot, Agus; Kabuhung, Anselmus; Jusran, Mokoginta; Suwarja, Suwarja (Media Penelitian dan Pengembangan Kesehatan, 2024)
Potential dangers in hospitals, apart from infectious diseases, there are also other potential dangers, namely accidents, radiation, anesthetic gasses, psychosocial and ergonomic disorders. The study aimed to analyze the implementation of potential dangers of hospital services using the method Job Safety Analysis at the Regional Hospital X. This type of research is descriptive. a sample of 7 people who work in the Emergency Unit, through an approach accidental sampling. The research variable is the potential for danger in the UGD Regional Hospital X. The instrument used is the JSA instrument. The data obtained is presented in the form of a narrative and a matrix of in-depth interview results. Respondents who carry out potentially dangerous work according to the JSA method are doctors and nurses who provide services in the Emergency Unit. The work carried out is lifting and moving patients, giving injections, using ventilators, using EKGs, using monitor units, using section units and workload. Respondents who carry out potentially dangerous work according to the JSA method are doctors and nurses. Potentially dangerous facilities are syringes, ventilators, sections, masks, stethoscopes, cuffs, EKGs, ventilators, section units. For the  Regional Hospital X to provide outreach about occupational safety and health management in the hospital to all employees so that they know the risk of work accidents and make an analysis of potential hazard methods according to the JSA method so that doctors and nurses know the level of risk of work accidents when providing services.